Pharmacist Intervention and Quality of Life of HIV-Infected Patients in Nigeria - Bello, Shakirat I (Bangladesh Pharmaceutical Journal, 2018)
Assessment of quality of life of HIV-infected patients on combined antiretroviral therapy (cART) is imperative in the management of the disease. This study was done to assess the quality of life (QOL) of HIV-infected patients on cART before and after the pharmacist intervention. Consented HIV diagnosed outpatients in a tertiary health care facility in Benin City that met inclusion criteria were consecutively enrolled into the study. The QOL of these patients was determined in the four domains of WHOQOLHIV BREF instrument. The raw scores for each domain in the WHOQOL-HIV BREF were calculated by adding values of single items. The scores were computed on the scale of 0 to 100. One way ANOVA and Student t-test were used to compare means. At baseline, mean QOL values were below 73. The lowest values were in the social domain and the best values in the physical domain. The QOL values increased steadily over the period of interventions with the highest mean QOL of 93.7 in the physical domain. The improvement in QOL was significant at 6 and 9 months following interventions (p < 0.001). The values obtained are expressed in percentage. There was no statistically significant difference between male and female patients on cART in all domains of QOL following the intervention. Patients on Tenofovir + Emtricitabine + Efavirenz combination therapy had significantly higher scores in all the domains of QOL as compared with other drug combinations used in the management of the patients. The only educational level of the patients was significantly associated with the patients’ QOL. The intervention in this prospective study was a success, as it led to increasing in QOL for the patients on cART from the baseline level to the end of the 9th month. Bangladesh Pharmaceutical Journal 20(2): 132-138, 2017